Evaluation of Use of Personal Protective Equipment for Health Care Workers In Hospital X Bantul - Nur Syarianingsih Syam; Selvi Novita Sari; Siti Kurnia Widi Hastuti (Faculty of Public Health, Sriwijaya University, 2020)
Hospitals are a high-risk workplace for the safety and health of Human Resources (HR). Control of sources and potential hazards in hospitals can be done with the use of Personal Protective Equipment (PPE). PPE consists of gloves, masks, face/eye protection, protective gowns, and leg protectors. The purpose of this study was to evaluate the use of PPE on health workers in Bantul X Yogyakarta Hospital. This research used descriptive qualitative method with a phenomenological design. Data collection used interview guidelines for 5 informants who were selected based on the purposive method or fulfillment of certain criteria and carried out the observation of the use of PPE to 30 health workers. The results of the research related to input indicate that there are policies and standard operating procedure for the use of PPE in nursing care actions. It is also known that health care workers have received information and training on how to use PPE and personal protective equipment were always available and in accordance with the indications of actions in the central operating room unit, inpatient room, and Central Sterile Supply Departement. The results of observations of the level of PPE use in health workers (the process of use masks used by 30 officers, gloves 24 officers, dresses/ aprons 15 officers, head cover 15 officers and no activities were found with an indication of the use of goggle at the time of observation. it can be concluded that the use of PPE in hospital X Bantul has not met Permenkes standards, both in terms of the number of users (output) and in terms of the use process.